Implementasi Model Ekonomi Berbasis Masyarakat dalam Pengelolaan Dana Desa sebagai Upaya Mewujudkan Visi Asta Cita Presiden di Desa Tertinggal - Nursam Nursam; Mohammad Sawir; Mudatsir (Indonesian Journal Publisher, 2026)
This study aims to evaluate the effectiveness of implementing a community-based economic model in the management of Village Funds in Tende Village, Galang District, Tolitoli Regency. The urgency of this research lies in the underutilization of Village Funds, which remain predominantly allocated to physical infrastructure rather than community economic empowerment. The research employed a Participatory Action Research (PAR) approach, involving village officials, the Village Consultative Body (BPD), the Activity Implementation Team (TPK), and community members as active stakeholders. Data were collected through focus group discussions (FGDs), in-depth interviews, participatory observation, and document reviews. The findings indicate a significant increase in community participation in village deliberations, rising from 42% to 71% following the model’s implementation. The pilot project on agricultural product processing also generated a 17% increase in members’ household income. Supporting factors include strong commitment from village authorities, the availability of local natural resources, and regulatory support. Conversely, major constraints consist of limited human resource capacity, restricted market access, and low managerial literacy. In conclusion, the community-based economic model has proven effective in enhancing Village Fund management and household economic independence, and it has the potential to be replicated in other villages with similar socio-economic characteristics.